Shared experiences, shared support: A qualitative study on the importance of relatability in interpersonal relationships for youth mental health in South Africa - Junita Henry; Fredric Azariah; Matt Hughsam; Sarah Skeen; Mark Tomlinson; Chuma Busakhwe; Khotso Mokoena; Almaaz Mudaly; Moitreyee Sinha; Christina Laurenzi (Cambridge Prisms: Global Mental Health)
Adolescence is a critical developmental period marked by significant changes, increasing the risk of mental health problems such as anxiety and depression. Understanding how youth engage with mental health resources is essential. This study explored the role of interpersonal relationships—including peer-to-peer, adult-youth, parent, teacher and mentor relationships, and interactions with mental health professionals—in shaping youth mental health engagement and identified factors influencing these relationships. Using a phenomenological qualitative design, youth researchers (YRs) and youth advisors (YAs) were engaged throughout the research process. Semi-structured interviews were conducted with South African youth aged 14–24 years. The study highlighted the significance of peer relationships, particularly relatability, as key in youth mental health support. Family relationships had a mixed role, with factors like lack of mental health literacy, age differences, and cultural norms hindering effective communication and support. By understanding the dynamics of these relationships, this study emphasizes the need for targeted interventions that harness social support. Enhancing the quality of relationships and promoting positive social bonds can protect against mental health problems. Addressing gaps in support by recognizing and supporting peer-to-peer engagement is essential. Findings provide valuable insights for designing strategies to promote mental well-being among youth, particularly in resource-constrained settings.